Creativity level of students in the course of collaborative flute jamming - Li, Yang (Música Hodie, 2023)
The key objective of the research is to determine a correlation between the level of creativity of students and their experience of jamming in groups on the basis of pre- and post-tests. A total of 260 respondents were divided into control and experimental groups (130 people each). In the course of the research, the students took a creativity test in the first, second, and third weeks of the experiment. Students from the experimental group rated the jamming process extremely positively. In particular, they reported that these practices improve mood and musical skills. The results obtained can be useful in the field of psychology and musicology and also serve as an argument for the introduction of jam sessions into the curriculum of higher educational institutions.